Implementasi Metode Drill dalam Pembelajaran Bahasa Arab di Madrasah Ibtidaiyah Ummusshabri - Fikri, Ahmad Futunul; Khofifah, Khofifah; Fauziah, Fauziah; Susilo, Akhbar (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2025)
This study aims to describe how the application of the drill method in Arabic language learning at the Madrasah Ibtidaiyyah Pesantren Ummusshbari Kendari. The type of research used is a qualitative descriptive approach using data collection techniques through interviews, observations and documentation. The data analysis method used by the author through three stages, namely data reduction, data presentation and drawing conclusions. The results of the study indicate that the application of the drill method in Arabic language learning at the Madrasah Ibtidaiyyah Pesantren Ummusshabri Kendari that teachers have implemented the drill method well in the learning process in the classroom. There are several stages that must be carried out by the teacher, namely the preparation stage, implementation of learning and evaluation of learning. Supporting factors are the availability of adequate facilities such as television and textbooks and a whiteboard. While the inhibiting factor is the lack of interest in learning for students. Further research can examine Arabic language learning based on differentiation as an effort to understand each student's ability in learning.